UKM Ber-NIB : Pemenuhan Dokumen NIB Melalui Online Single Submission bagi Petani Jamur Selorejo Blitar - Setyawati, Dyah; Ariyanti, Ariyanti; Santi, Fitriana; Cahya, Regina Heart Dwi; Primadani, Eka Intan (JAST : Jurnal Aplikasi Sains dan Teknologi, 2023)
Mushroom farmers are part of Small and Medium Enterprises (UKM) involved in mushroom cultivation, established in 2019. Continuously engaging in development and ongoing improvements, this SME considers the geographical location of the Selorejo Blitar area highly suitable for mushroom cultivation. Efforts to improve management and administration are consistently made, with the hope that the business will operate smoothly alongside administrative compliance. Given these conditions and recognizing the importance of legality for business operators, the community service team contributes to mushroom farmers by providing training on obtaining the Business Registration Number through the Online Single Submission (OSS) system. The result of this community service activity is that mushroom farmers not only fulfill their administrative requirements but also legally register their businesses with the Ministry of Industry and Trade. This registration brings additional benefits, such as access to government services, ease of banking ABSTRAKPetani Jamur merupakan salah satu UKM yang bergerak dibidang Pertanian Jamur dan berdiri pada tahun 2019. UKM ini terus menerus melakukan pengembangan dan perbaikan berkelanjutan mengingat lokasi geografis area Selorejo Blitar sangat sesuai dengan komoditas Jamur ini. Upaya perbaikan manajemen dan adminstrasi juga selalu dilakukan dengan harapan usaha akan berjalan seimbang dengan pemenuhan administrasi. Berdasar kondisi tersebut dan mengingat pentingnya legalitas bagi pelaku usaha, maka tim pengabdi hadir dengan berkontribusi terhadap Petani Jamur dengan memberikan pelatihan bagaimana mendapatkan Nomor Induk Berusaha melalui sistem OSS (Online Single Submission). Hasil dari kegatan pengabdian masyarakat ini yaitu pelaku Petani Jamur tidak hanya melengkapi kebutuhan administrasi tetapi juga secara legal usahanya terdaftar di Kementrian Perindustrian dan Perdagangan serta memperoleh kemudahan-kemudahan lain seperti akses layanan pemerintah, kemudahan transaksi perbankan, kredibelitas, kepatuhan regulasi, peluang pasar, fasilitas pajak serta integrasi data.